Test Bench for Experimental Analysis of Conductive Composite Materials for Aerospace Applications. - Pham, N. N.; Leuchter, J.; Václavík, J. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
The paper presents the materials used in aerospace industry and introduces an automated test bench for investigating these materials’ electrical properties. The test bench is also designed to investigate aviation electronic components, especially regarding electromagnetic compatibility (EMC). The test bench contains various measuring instruments which are connected to a computer (workstation). The designed program on the computer supervises identifying connected instruments and creating communication channels to those instruments. This program also controls those instruments to conduct required measurement or testing and obtain the measuring results. Instrument control is realized by using Standard Command for Programable Instrument (SCPI) commands. The program is designed in MATLAB development environment and add-on application MATLAB App Designer with toolboxes Instrument Control Toolbox and Signal Processing Toolbox.
Keywords: Aerospace Industry; Conductive Composite Material; MATLAB; SCPI